2022
DOI: 10.1055/s-0042-1758753
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and medication effect in mild-stage subjects with Parkinson's disease

Abstract: Background Parkinson's disease (PD) causes a series of movement disorders, many of them starting in the early stage. Objective To analyze the pulmonary function of mild-stage subjects with PD and to investigate the effects of levodopa on it. Methods We included 21 patients with idiopathic PD and 20 healthy control subjects. The participants were submitted to spirometry and impulse oscillometry assessments. The PD patients were evaluated during the “off” and “on” phases of their anti-PD medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
2
0
2
Order By: Relevance
“…The review of Pokusa et al ( 2020) 39 is in line with authors who cited pulmonary complications of PD as the most frequent cause of death in this population 10,11,19,38,40 . This study also points out the impairment of the respiratory system even in the early stages of the illness, when the diagnosis tends to be complicated and masked by other symptoms.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The review of Pokusa et al ( 2020) 39 is in line with authors who cited pulmonary complications of PD as the most frequent cause of death in this population 10,11,19,38,40 . This study also points out the impairment of the respiratory system even in the early stages of the illness, when the diagnosis tends to be complicated and masked by other symptoms.…”
Section: Discussionsupporting
confidence: 57%
“…Our protocol of assessments and intervention was executed after one hour levodopa intake to ensure the period ON of all patients. Despite being the gold standard for treating motor disorders, there is debate about its role in treating respiratory dysfunction in PD, as Oliveira et al ( 2022) stated that the effect of levodopa on respiratory function is not significant in PD patients at the mild stage 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent with previous study, our data did not show any ventilation dysfunction in mild PD. Oliveira et al [21] reported that the spirometric scores indicate an incipient obstructive disorder in mild PD. This may be because the results of the respiratory function parameters in their study were measured during the "off" phase of the medication.…”
Section: Discussionmentioning
confidence: 99%
“…Seguiram-se as recomendações da American Thoracic Society (GRAHAM et al, 2019) e foram avaliados parâmetros como: volume total (ToV), volume corrente (Vt), capacidade vital forçada (CVF), relação VEF1/CVF, pico de fluxo expiratório (PFE) etc. Os autores demonstraram que a complacência pulmonar e aresistência, na fase inicial da doença, são comparáveis aos parâmetros normais (indivíduos sem doença) ao oscilômetro de impulso, com presença de um distúrbio obstrutivo incipiente à espirometria em pacientes com DP(OLIVEIRA et al, 2022). Não foi encontrado efeito significativo da medicação anti-DP na função pulmonar dos pacientes; porém, os pesquisadores hipotetizaram que a não interferência da L-DOPA nos resultados seja em grande parte decorrente do perfil escolhido para a amostra (sem doença respiratória significativa prévia).…”
unclassified
“…Não foi encontrado efeito significativo da medicação anti-DP na função pulmonar dos pacientes; porém, os pesquisadores hipotetizaram que a não interferência da L-DOPA nos resultados seja em grande parte decorrente do perfil escolhido para a amostra (sem doença respiratória significativa prévia). A conclusão a que se chegou foi a de que, em indivíduos na fase leve da doença, o efeito da levodopa sobre o sistema respiratório não é significativo(OLIVEIRA et al, 2022).O tratamento com a levodopa pode produzir efeitos dramáticos em todos os sinais e sintomas da DP. Nos estágios iniciais da evolução da doença, o grau de melhora do tremor, da rigidez e da discinesia promovidos pelo uso da carbidopa/levodopa pode ser de quase 100%.…”
unclassified